#### Answer

$$-i\sqrt2-2-(6-4i\sqrt2)-(5-i\sqrt2)=-13+4i\sqrt2$$

#### Work Step by Step

$$A=-i\sqrt2-2-(6-4i\sqrt2)-(5-i\sqrt2)$$
$$A=-i\sqrt2-2-6+4i\sqrt2-5+i\sqrt2$$
Now, adding or subtracting complex number means we add and subtract the real parts and the imaginary parts separately.
In other words, the real parts are put into a parenthesis, while the imagine parts are put into another parenthesis to do the math separately.
$$A=(-2-6-5)+(-i\sqrt2+4i\sqrt2+i\sqrt2)$$
$$A=-13+(-\sqrt2+4\sqrt2+\sqrt2)i$$
$$A=-13+(4\sqrt2)i$$
$$A=-13+4i\sqrt2$$